The Rapid Analysis of Heroin Drug Seizures Using Micellar Electrokinetic Chromatography with Short-End Injection - Anastos, N.; Lewis, Simon; Barnett, N.; Pearson, J.; Kirkbride, K. (Blackwell Publishing, 2005)
A simple and rapid method for the analysis of heroin seizures by micellar electrokinetic chromatography with short-end injection is described. Separations were performed using an uncoated fused silica capillary, 50 cm×50µm I.D.×360µm O.D. with an effective separation length of 8 cm. The system was run at 25?C with an applied negative voltage of –25 kilovolts. Injection of each sample was for 2 s at –50 mbar. UV detection was employed with the wavelength set at 210 nm. The background electrolyte consisted of 85:15 water:acetonitrile, v/v) containing final concentrations of 25mMSDS and 15mMsodium borate, pH 9.5. Samples and standards were prepared in 0.1% v/v acetic acid and diluted in the run buffer containing 1 mg/ml of N,N-dimethyl-5-methoxytryptamine as an internal standard. Under these conditions a text mixture containing caffeine, paracetamol, morphine, codeine, heroin, and acetylcodeine was resolved within 1.5 min. The method was used to determine the concentration of heroin in heroin seizure samples, and the results were in good agreement with those obtained by a validated gas chromatographic method.